Studi Komparatif Pembelajaran Pendidikan Agama Islam pada Sekolah Formal Berbasis Boarding School dan Pondok Pesantren: Studi di MAN 1 Kota Malang dan MA An Nur Bululawang: A Comparative Study of Islamic Education in Formal Schools Based on Boarding Schools and Islamic Boarding Schools (Study in Man 1 Malang City and Ma An Nur Bululawang-Malang) - Moch. Nur Alimin; Siti Nailatur Roihana (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
The world of education today confronts challenges associated with individuals of noble character. There are problems along with the development of the times, including juvenile delinquency, promiscuity, brawls between students, and moral degradation. Related to this phenomenon, nowadays there are rampant formal institutions (formal schools), which also have boarding schools and Islamic boarding schools. The institution was established in an effort to improve Islamic education, which also contains morals. The focus of this research problem has been directed to the study of (1) Islamic education in boarding school-based formal schools (MAN 1 Malang City), (2) Islamic education in islamic boarding school-based formal schools (MA An Nur Bululawang-Malang), and (3) characteristics of Islamic education in boarding school-based formal schools (MAN 1 Malang City) and islamic boarding schools (MA An Nur Bululawang-Malang). The method used in this study is a qualitative approach (comparative study). The data analysis used involves analyzing all existing data, reducing data, compiling data into units, and categorizing data. The last stage carried out is to check the validity of the data. Based on the results of the study, it can be concluded. (1) Islamic education in boarding school-based formal schools (MAN 1 Malang City) has a level of effectiveness of Islamic education both in terms of quality and quantity. (2) Islamic education in formal boarding school-based schools (MA An Nur Bululawang-Malang) has become a tradition/culture, formal schools adopt Islamic education values sourced from Islamic boarding schools, (3) The characteristics of Islamic education in boarding school-based formal schools occur The balance between religious and general knowledge, the margin between the two, is not too large. Meanwhile, Islamic education in formal boarding school-based schools adopts boarding values in every activity at school.